2019
DOI: 10.1590/0100-3984.2018.0013
|View full text |Cite
|
Sign up to set email alerts
|

The many faces of primary and secondary hepatic lymphoma: imaging manifestations and diagnostic approach

Abstract: Hepatic lymphoma can be divided into its primary and secondary forms. To be classified as primary hepatic lymphoma, the disease should be limited to the liver and hilar lymph nodes, with no distant involvement (to the bone marrow or other sites). Primary hepatic lymphoma is quite rare, accounting for less than 1% of all cases of non-Hodgkin lymphoma, whereas secondary hepatic lymphoma affects nearly half of such cases. Familiarity with the imaging features of hepatic lymphoma is important for its early diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 10 publications
(20 reference statements)
0
25
0
Order By: Relevance
“…Evaluation of the liver by imaging methods has been the subject of various recent studies in the radiology literature of Brazil (28)(29)(30)(31)(32) . The availability of affordable, good quality ultrasound machines has allowed the development of focused point-of-care ultrasound protocols applicable to tropical diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the liver by imaging methods has been the subject of various recent studies in the radiology literature of Brazil (28)(29)(30)(31)(32) . The availability of affordable, good quality ultrasound machines has allowed the development of focused point-of-care ultrasound protocols applicable to tropical diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in the radiology literature of Brazil have emphasized the importance of imaging examinations in the evaluation of hepatic neoplasms (18)(19)(20)(21)(22)(23) . The present study used the LI-RADS classification system to analyze 38 patients infected with hepatitis viruses (HBV, HCV, HDV, or combinations thereof) who underwent CT. We found that approximately 32% of the patients presented with LI-RADS 5 observations (i.e., lesions diagnosed by imaging as classic HCC).…”
Section: Discussionmentioning
confidence: 99%
“…There are several imaging features of PHL which may help to differentiate it from other more common liver malignancies. First, PHL may present with three distinct morphologic patterns; the most common being a single, well-defined lesion in 64% of cases [48,49]. The other two less common forms include multiple discrete lesions or a diffuse, miliary pattern [48,49].…”
Section: Primary Hepatic Lymphomamentioning
confidence: 99%
“…First, PHL may present with three distinct morphologic patterns; the most common being a single, well-defined lesion in 64% of cases [48,49]. The other two less common forms include multiple discrete lesions or a diffuse, miliary pattern [48,49]. On ultrasound, PHL most often appears as an homogeneous hypoechoic lesion with well-defined margins [50].…”
Section: Primary Hepatic Lymphomamentioning
confidence: 99%
See 1 more Smart Citation